2012
DOI: 10.1111/are.12041
|View full text |Cite
|
Sign up to set email alerts
|

Early development and allometric growth in hatchery-reared characinBrycon orbignyanus

Abstract: The characin piracanjuba, Brycon orbignyanus (Valenciennes, 1850), has been recognized as a candidate species for aquaculture. The early morphological development and allometric growth of hatchery‐reared piracanjuba were studied from hatching to the juvenile stage, at water temperature of 27.9 ± 0.6°C. Growth, in total length (TL), was linear during that period. At hatching (3.4 ± 0.2 mm TL), the non‐pigmented free embryo had most functional systems not fully differentiated. The primordial finfold was almost c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
(62 reference statements)
6
8
0
2
Order By: Relevance
“…Positive tail allometry is mostly related to development of the caudal fin and ossification of fin rays (Betti et al, ; Maciel et al, ). Trunk length ( L Tr ) showed a negative allometric growth pattern for up to 7 dph, which is similar to other teleosts (Osse & van den Boogaart, ; Osse & van den Boogaart, ; Nogueira et al, ). Osse & van den Boogaart () suggested that rapid growth of the head and tail could be associated with the reduction of drag on the body and improvement of swimming ability.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Positive tail allometry is mostly related to development of the caudal fin and ossification of fin rays (Betti et al, ; Maciel et al, ). Trunk length ( L Tr ) showed a negative allometric growth pattern for up to 7 dph, which is similar to other teleosts (Osse & van den Boogaart, ; Osse & van den Boogaart, ; Nogueira et al, ). Osse & van den Boogaart () suggested that rapid growth of the head and tail could be associated with the reduction of drag on the body and improvement of swimming ability.…”
Section: Discussionsupporting
confidence: 84%
“…Allometric growth was calculated using simple linear regressions according to the equation log y = log a + b log L T , where y is L H , L Tr , L Ta , D B , D E , L Sn , a is the intercept and b is the growth coefficient. We considered growth as isometric when b = 1, positively allometric when b > 1 and negatively allometric when b < 1 (Huxley, ; Nogueira et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Ho wever, swimbladder inflation and exogenous feeding slightly preceded yolk sac depletion in A. chalcoides. Similar developmental pattern is also found in zebrafish Danio rerio (Kimmel et al, 1995), angelfish Pterophyllum scalare (Zilberg et al, 2004), black skirt tetra Gymnocorymbus ternetzi (Çelik et al, 2011) and characin Brycon orbignyanus (Nogueira et al, 2014). On the other hand, the mixed nutrit ion period of A. chalcoide lasted only one day, which is slightly longer than that of black skirt tetra Gymnocorymbus ternetzi (less than 1 day at 24 ± 1°C) (Çelik et al, 2011), but is shorter than that of Chinese sturgeon Acipenser sinensis (2 days at 15.5±0.5°C) (Chai et al, 2011), European hake Merluccius merluccius (4 days at around 12 °C) (Bjelland and Skiftesvik 2006) and grey mu llet Chelon labrosus (9 days at 16 °C) (Khemis et al, 2013).…”
Section: Morphological Developmentsupporting
confidence: 61%
“…Obviously, this behavior must be related to the development of tail region, which would contribute to improving swimming ab ility and predator avoidance (Fuiman 1983). In contrast, the trunk growth in length (TRL) showed negative allo metry (b=0.48) during early life stage (fro m hatching to 25-29 DAH), indicat ing that trunk segment is co mpleted early in emb ryogenesis or yolksac stage and the number o f myoto mes does not increase further after that stage (Gisbert and Doroshov 2006;Nogueira et al, 2014). This growth pattern that the anterior and posterior parts of the body grew faster than the middle section was not surprising, as it is common for many fish species (Fuiman 1983;van Sn ik et al, 1997;Gisbert 1999;Gisbert et al 2002;Nogueira et al, 2014;Gisbert et al, 2014;Kupren et al, 2014a;b).…”
Section: Allometric Growthmentioning
confidence: 99%
See 1 more Smart Citation